118: PROGNOSTIC SIGNIFICANCE OF EXTRACAPSULAR LYMPH NODE INVOLVEMENT AFTER GASTRECTOMY FOR GASTRIC ADENOCARCINOMA. (23rd April 2022) - Prasad, P; Chmelo, J; Wahed, S; Navidi, M; Phillips, A
Abstract: Background and aim: Lymph node involvement is a key prognostic indicator in gastric adenocarcinoma. Little is known of the impact of extracapsular lymph node involvement (LNI) upon the prognosis of patients undergoing curative resection of gastric cancer. The aim of this study was to assess the incidence and prognostic significance of extracapsular LNI in patients undergoing a gastrectomy for gastric adenocarcinoma. Methods: Consecutive patients who underwent a subtotal or total gastrectomy with curative intent for adenocarcinoma of the stomach or gastro-oesophageal junction in a single, high-volume U.K. centre between 2010 and 2018 were identified from contemporaneously maintained database. Patients with a pN0 status on final histology and those who died in-hospital were excluded from analysis. Factors associated with survival were studied with univariable and multivariable cox regression analysis. A P value of <0.05 was deemed significant. Results: The study included 235 patients. A median (IQR) of 32 (24–43) lymph nodes were resected and median (IQR) 4 (1–9) lymph nodes were positive. Of them, extracapsular LNI was identified in 123 (52%) of patients. Factors associated with survival on univariable analysis were R1 resection ( P  = 0.001), p/ypT stage ( P  < 0.001), p/ypN stage ( P  < 0.001) and extracapsular LNI ( P  = 0.001). Median survival among patients who had extracapsular LNI was 19 months versus 49 months among patients who did not ( P  < 0.001). Extracapsular LNI was not an independent predictor of survival on multivariable analysis ( P  = 0.535). Conclusion: Extracapsular LNI is associated with poor prognosis among patients undergoing a curative gastrectomy. However, it is not an independent predictor of survival among this patient cohort.